Exploring Contemporary Issues in Sexuality Education with Young People Theories in Practice - Quinlivan, Kathleen (Palgrave Studies in Gender and Education, 2018)
This book explores contemporary issues in sexuality and relationship education for young people. Drawing upon rich empirical and ethnographic research undertaken with students and teachers in secondary schools, the author asks how school-based sexuality education can better equip young people to engage with contemporary social, political and cultural sexuality and relationships issues. Creatively working across both theoretical and practical contexts, this accessible work suggests approaches to sexuality and relationships education that can build upon the ways in which young people are developing a sense of identity; the ultimate aim being to help them to meet their emotional, spiritual and relational potential. Challenging established approaches to sexuality education, this thought-provoking book shines a new light on alternative perspectives that can help make sexuality and relationships education more relevant and meaningful for young people in a rapidly changing world. This volume will be of interest and value to students and scholars of sexuality and relationship education, as well as practitioners.